2012
DOI: 10.1167/iovs.11-9031
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Acetylcholine Receptor 3 Is Dominant in Myopia Progression

Abstract: PURPOSE. Numerous studies have proven that the nonselective muscarinic acetylcholine receptor (mAChR) antagonist atropine prevents the axial elongation that leads to myopia. Five distinct receptor genes (CHRM1-CHRM5), each encoding a muscarinic receptor protein (M[1]-M[5]), have been cloned. Copy number variations (CNVs), which constitute a substantial portion of genetic variability and structural genetic variants, are increasingly being recognized as modulators of human diseases. In this study, CNVs of CHRMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…In this same study, suppression of dopaminergic retinal pathways by intravitreal injection of a neurotoxin restored the growth inhibition at night in these chickens . The evidence for dopamine and melatonin playing a role in eye growth is preliminary and other neuromodulators such as glucagon and acetylcholine may be involved. It is conceivable that interrupting diurnal rhythm by exposing turkeys in our study to a prolonged photoperiod led to disturbances in dopamine and melatonin, which in turn resulted in excessive ocular growth.…”
Section: Discussionmentioning
confidence: 65%
“…In this same study, suppression of dopaminergic retinal pathways by intravitreal injection of a neurotoxin restored the growth inhibition at night in these chickens . The evidence for dopamine and melatonin playing a role in eye growth is preliminary and other neuromodulators such as glucagon and acetylcholine may be involved. It is conceivable that interrupting diurnal rhythm by exposing turkeys in our study to a prolonged photoperiod led to disturbances in dopamine and melatonin, which in turn resulted in excessive ocular growth.…”
Section: Discussionmentioning
confidence: 65%
“…Bardzo ważna zatem jest ocena, czy pacjent ma nadmierną akomodację, czy też niedomogę akomodacji. Drugi ważny mechanizm działania tego leku to jego oddziaływanie na receptory muskarynowe fibroblastów twardówki i jej wpływ na przemodelowanie struktury twardówki (5,16).…”
Section: Leczenie Farmakologiczne Krótkowzrocznościunclassified
“…Although earlier studies have suggested that atropine may achieve this due to its effects on lens accommodation, more recent studies have shown that the main mechanism is via non-accommodative pathway especially acting directly on receptors in the sclera [3,6,7] which slows axial elongation. Nevertheless, unavoidable side effects of atropine such as near vision blur, photophobia, and glare and rebound after discontinuing treatment which are seen particularly in higher doses have limited its utilization.…”
Section: Pharmacological Controlmentioning
confidence: 99%
“…The non-accommodative mechanisms such as creating a myopic shift in the peripheral retina and altering corneal shape by optical interventions [3][4][5], and scleral collagen enhancement by pharmacological agents [3][4][5][6] have gained popularity in myopia control, and significant beneficial outcomes have been reported by many reserachers. This mini-review aimed specifically at investigating the comparative effectiveness of different interventions systematicaly and summarizing data on the myopia control in children from recent studies.…”
Section: Introductionmentioning
confidence: 99%